Dasar-dasar Pendidikan akhlak dalam Al-Quran Menurut Surat Al-Araf Ayat 199-202 - Ernawati Sulhatul Imamah (E-Jurnal Aksioma Ad-Diniyyah : The Indonesian Journal of Islamic Studies, 2014)
This study aims to 1) explain the method of interpretation of Wahbah az-Zuhaili concerning al-Qur'an surat al-A'raf verses 199-2022) find the basics of moral education in the Qur'an Surat al-A'raf verse 199 -202 by examining Tafsir al-Munirfīal-'Aqīdah wa al-Shari'a a al-Manhaj. The usefulness and usefulness of this research is to add information and hazanah of Islamic thought, especially in the field of tafsir, which is expected to add to the knowledge of moral education contained in surat al-A'raf verses 199-202. This type of research is classified as library research. The approach used is a qualitative approach, namely the type of research whose findings are not obtained through statistical procedures or other forms of calculation. The research is descriptive analytical. The primary sources used are Tafsir al-Munirfīal-qAqīdah wa al-Syarī'ah wa al-Manhājdan l-Qur'an translation. As for the data collection method used is documentation. This study uses content analysis. The results of this study indicate that 1) The method used by Wahbah az-Zuhaili when explaining is the muqarin method (compromising between ma'ṡurdan ma'qul). Ma'ṡur is the history of the hadith of the Prophet and the statement of the salafus-salehsedangkan ma'qul is in accordance with the rules that have been recognized2) The Basics of Moral Education in the Qur'an Al-A'raf verse 199-202 is an attitude of forgiveness, doing ma'ruf, turning away from the temptations of Satan, taking refuge in Allah from the temptations of Satan, always seeing his own mistakes and not being friends with Satan (friends with godly people).  Penelitian ini bertujuan untuk 1) menjelaskan metode penafsiran Wahbah az-Zuhaili mengenai al-Qur’an surat al-A’raf ayat 199-2022) menemukan dasar-dasar pendidikan akhlak dalam al-Qur’an surat al-A’raf ayat 199-202 dengan mengkaji Tafsīr al-Munīrfīal-‘Aqīdah wa al-Syarī’ah a al-Manhāj.Manfaat dan kegunaan penelitian ini adalah untuk menambah informasi dan hazanah pemikiran Islam khususnya di bidang tafsirdandiharapkan dapat menambah pengetahuan embaca erkait dasar-dasar pendidikan akhlak yang terkandung dalam surat al-A’raf ayat 199-202. Jenis penelitian ini tergolong penelitian kepustakaan (library research).Pendekatan yang digunakan dalah pendekatan kualitatif yaitu jenis penelitian yang hasil temuannya tidak diperoleh melalui prosedur statistik atau bentuk hitungan lainnya. Penelitian ini bersifat deskriptif analitis.Sumber ata primer yang digunakan adalah Tafsīr al-Munīrfīal-‘Aqīdah wa al-Syarī’ah wa al-Manhājdan l-Qur’an terjemah.Adapun metode pengumpulan data yang digunakan adalah dokumentasi. enelitian ini menggunakan analisis isi (contentanalisys). Hasil penelitian ini menunjukkan bahwa 1) Metode yang digunakan Wahbah az-Zuhaili ketika menjelaskan adalah metode muqarin(mengompromikan antara ma’ṡurdan ma’qul). Ma’ṡuradalah riwayat dari hadis Nabi dan erkataan para salafus-salehsedangkan ma’quladalah yang sesuai dengan kaidah-kaidah yang elah iakui2) Dasar-dasarPendidikan Akhlak dalam al-Qur’an Surat al-A’raf ayat 199-202 adalahSikap emaaf, berbuat ma’ruf, berpaling dari godaan setan, berlindung kepada Allah dari godaan setan, selalu melihat kesalahan sendiridan tidak berteman dengan setan (berteman dengan orang yang saleh).